The Effect of Stock Recording Digitalization and the Application of the FIFO Method on the Perception of Expired Product Losses at SpiceBali - Dwi Naba Setia Amara; Ni Komang Prasiani; Putu Astri Lestari (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study examines the effect of stock recording digitalization and the application of the First in First Out (FIFO) method on the perception of expired product losses at SpiceBali, a spice distributor in Bali that recorded annual losses of Rp 70–150 million due to expired products in 2023. The research applies a quantitative associative-causal approach using multiple linear regression analysis, with primary data collected through questionnaires administered to 40 employees involved in inventory management, supplemented by secondary data from monthly internal loss reports covering the 2023–2025 period. The findings reveal that stock recording digitalization (β = 0.310; t = 4.609; p < 0.001) and the FIFO method (β = 0.374; t = 4.922; p < 0.001) each exert a significant positive influence on the perception of expired product losses, with both variables jointly explaining 53.4% of the variance (F = 21.171; p < 0.001). Secondary data analysis further corroborates these results, showing that average monthly losses declined from Rp 12,441,667 in 2023 to Rp 3,925,000 in 2025, representing a cumulative reduction of 68.45%, confirmed as statistically significant across all periods by Repeated Measures ANOVA (F = 666.945; η² = 0.984) and Bonferroni-corrected post-hoc tests. These results indicate that the combined implementation of digitalization and FIFO delivers a sustained and progressively strengthening impact on inventory efficiency, consistent with a learning curve effect. The study contributes empirical evidence on the effectiveness of technology-driven inventory management strategies in reducing perishable product losses within the distribution sector. Keywords: stock recording digitalization, FIFO method, expired product losses, inventory management, perishable goods.